MPC & ADRC Control for robots - Makhloufi Hibat Erahmane; Sahli Abdelnaceur; Mohammed Belkhiri (University of Amar Telidji - Laghouat Faculty of Technology Department of Electronics, 2022)
This project addresses the tracking control problem of a quadrotor with model uncertainties and external disturbances. First, the Newton-Euler approach is used to build the quadrotor mathematical model. Then, the MPC is applied successfully to the linearized decoupled subsystems of the drone based on two decentralization approaches. The high gain observer was used to estimate the quadrotor disturbances and integrated to the prediction model of MPC. Finally, simulation results show that the quadrotor can track the reference trajectory effectively even in the presence of disturbances.
OPTION: Automation & Industrial Computing